It is currently 18 Nov 2017, 03:59

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Solve This!

Author Message
Senior Manager
Joined: 30 Aug 2003
Posts: 328

Kudos [?]: 26 [0], given: 0

Location: BACARDIVILLE

### Show Tags

26 Jan 2004, 17:44
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Solve sqrt(5x^2 - 6x + 8) - sqrt(5x^2 - 6x - 7) = 1
_________________

Pls include reasoning along with all answer posts.
****GMAT Loco****
Este examen me conduce jodiendo loco

Kudos [?]: 26 [0], given: 0

Manager
Joined: 26 Dec 2003
Posts: 227

Kudos [?]: 3 [0], given: 0

Location: India

### Show Tags

26 Jan 2004, 17:57
Pretty long calculation, uffffffffffff taking - sqrt 5x^2-6x-7 to the otherside and squaring both sides and then after cancelling some terms we get 7=sqrt 5x^2-6x-7 again squaring both sides we get 5x^2-6x-56=0 solve for x we get 4 and -14/5

Kudos [?]: 3 [0], given: 0

Senior Manager
Joined: 30 Aug 2003
Posts: 318

Kudos [?]: 29 [0], given: 0

Location: dallas , tx

### Show Tags

26 Jan 2004, 21:12
It is not clear rakesh..would u mind to show me stepwise..if its not bothering u much.. coz i am getting soemting diff..
_________________

shubhangi

Kudos [?]: 29 [0], given: 0

Manager
Joined: 26 Dec 2003
Posts: 227

Kudos [?]: 3 [0], given: 0

Location: India

### Show Tags

26 Jan 2004, 21:22
sqrt (5x^2-6x+8) - sqrt (5x^2-6x-7) =1 is the question
taking the term - sqrt(5x^2-6x-7) to other side we get
sqrt (5x^2-6x+8) = 1 + sqrt (5x^2-6x-7)
Now squaring on both sides we get

5x^2-6x+8 = 1 + 5x^2 -6x-7 + 2sqrt(5x^2-6x-7)
we can cancel out 5x^2 and -6x, then we get 14= 2sqrt(5x^2-6x-7)
which means , 7 = sqrt(5x^2-6x-7) , now squaring again we get 49= 5x^2-6x-7, ie 5x^2-6x-56=0 now solve for x

Kudos [?]: 3 [0], given: 0

Intern
Joined: 05 Jan 2004
Posts: 3

Kudos [?]: [0], given: 0

Location: VIRGINIA

### Show Tags

30 Jan 2004, 13:50
Let 5x^-6x+8 = A
Therefore sqrtA-sqrt (A+5)=1
squaring both sides:
A+A-15-2*sqrt(A^2-15*A)=1
transferring:
2A-16=2*sqrt(A^2-15*A)
factoring by 2:
A-8=sqrt(A^2-15*A)
squaring again:
=>A^2-16*A+64=A^2-15*A
=>A=64
=>5X^2-6X+8 = 64
=>5X^2-6X-56=0
=>(5X+14)(X-4)=0
=>X= 4, -14/5

Kudos [?]: [0], given: 0

30 Jan 2004, 13:50
Display posts from previous: Sort by

# Solve This!

Moderator: chetan2u

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.